Welcome Message from the Editors (CSIAM Transactions on Applied Mathematics, 2020)
Dear CSIAM-AM Reader:On behalf of the editorial board and the China Society for Industrial and AppliedMathematics (CSIAM), it is our pleasure to welcome you to the first issue of the CSIAMTransactions on Applied Mathematics (CSIAM-AM). The goal of CSIAM-AM is to provideyou, the valuable reader, with original research articles or reviews of high quality on atopic in applied mathematics that highlight the key role of mathematics in advancingmodern science and technology.The journal comes at the most exciting and critical time for applied mathematics asits relevance has never been so clear. The rapid developments of big data and artificiallyintelligence have greatly expanded the application scope of applied mathematics, andpresented unprecedented opportunities and challenges to applied mathematics. CSIAM-AM grows out of the strong demand of a quality platform for communicating significantresearch findings in applied mathematics that address interesting and challenging scientific problems. It will also be the flagship journal of CSIAM, a fast-growing society withover 10,000 individual non-student members.The objective of CSIAM-AM is to publish only quality manuscripts and to maintainthe quality as we move on. As an important step to achieve the objective, we are fortunate to have a distinguished group of mathematicians as our founding members of theeditorial board. Since the reception of the first submission in February 2019, the initialresponse of the journal has been overwhelming. We hope the journal will continue toreach to the right audience and expand our reader group.Finally, we would like to take the opportunity to acknowledge the help of many individuals over the course of launching the journal. In particular, the inauguration issuewould not be possible without the generosity of the board members and reviewers whohandled the first wave of submissions in a timely fashion, the staffs of the Global SciencePress and CSIAM for their professional assistance, and members of the CSIAM Committee on Publications for their efforts.Please enjoy the issue and we look forward to your future submissions.Sincerely,Pingwen Zhang, Editor-in-Chief and President of CSIAMGang Bao, Managing EditorCSIAM Transactions on Applied Mathematics